Research progress of nano selenium in the treatment of oxidative stress injury during hepatic ischemia-reperfusion injury - Deng, Xin; Ouyang, Peng; Xu, Wei; Yang, Erhua; Bao, Zhen; Wu, Yijing; Gong, Jin; Pan, Jinghua (Frontiers in Pharmacology, 2023)
Hepatic ischemia-reperfusion injury (HIRI) is an additional injury to ischemic tissue after hepatic revascularization, and its pathological mechanism is complex. HIRI is not only involved in the molecular targets that mediate cell death, such as ion channel activation, abnormal protease activation and mitochondrial dysfunction, but also related to the down-regulation of endogenous protective signals. As a by-product of normal aerobic metabolism, reactive oxygen species (ROS) act as a multi effect physiological signal factor at low concentration. However, liver ischemia-reperfusion will lead to excessive ROS accumulation, destroy redox homeostasis, lead to oxidative stress, cause cell death through a variety of mechanisms, and drive the further damage of ischemic liver. Recent studies have found that the antioxidant treatment of nano selenium can reduce the excessive production of ROS and play a potential protective role in reducing HIRI. This paper reviews the molecular mechanism of the antioxidant effect of nano selenium for the prevention and treatment of HIRI, in order to provide further experimental basis for the clinical prevention and treatment of HIRI.